Bacteriological Profile and their Susceptibility Pattern in Neonatal Intensive Care Unit at Tertiary Care Hospital in Wah - Saba Mushtaq , Sohail Ashraf , Lubna Ghazal , Rida Zahid , Basharat Hussain , Jamil, Saba Mushtaq , Sohail Ashraf , Lubna Ghazal , Rida Zahid , Basharat Hussain , Jamil (Journal of Rawalpindi Medical College, 2020)
Introduction: Neonatal sepsis is a clinical syndrome characterized by multiple symptoms and signs of infection during the first month of life. The objective of this study is to determine the frequency of commonly isolated bacteria from patients of neonatal sepsis and their susceptibility patterns in POF hospital at Wah. Methods: This cross-sectional study was carried out in POF Hospital Neonatal intensive care unit and Microbiology laboratory from January 2018 to December 2019. The blood samples of patients suspected with neonatal sepsis were processed as per standard methodology. Results: Out of ninety blood samples, fifty-one (56.7%) yielded the growth of Gram-negative rods and thirty-nine (43.3%) yielded Gram-positive cocci. Among Gram-positive bacteria, coagulase-negative staphylococci were the most common pathogen isolated from 53.8% cases followed by methicillin-resistant Staphylococcus aureus (15.3%). Among Gram-negative bacteria, Klebsiella pneumoniae (54.90%) was the most frequently identified bacteria followed by Serratia marcescens (27.45%). The Gram-positive cocci were the most susceptible to linezolid (100%) followed by vancomycin (87.2%). The Gram-negative rods depict remarkable resistance to ciprofloxacin (92.2%), gentamicin (100%), and meropenem (54.9%). Conclusions: The study concluded a predominance of Gram-negative bacteria as a causative agent of neonatal sepsis in our setup. The bacterial isolates are highly resistant to commonly prescribed oral as well as injectable antibiotics. Implementation of infection control policies is a dire need to combat the grave situation of increasing antibiotic resistance.